Modulation of nitric oxide synthase activity in macrophages - P. G. Jorens; K. E. Matthys; H. Bult (Mediators of Inflammation)
L-Arginine is converted to the highly reactive and unstable nitric oxide (NO) and L-citrulline by an enzyme named nitric oxide synthase (NOS). NO decomposes into other nitrogen oxides such as nitrite (NO2−) and nitrate (NO3−), and in the presence of superoxide anion to the potent oxidizing agent peroxynitrite (ONOO−). Activated rodent macrophages are capable of expressing an inducible form of this enzyme (iNOS) in response to appropriate stimuli, i.e., lipopolysaccharide (LPS) and interferon-γ (IFNγ). Other cytokines can modulate the induction of NO biosynthesis in macrophages. NO is a major effector molecule of the anti-microbial and cytotoxic activity of rodent macrophages against certain micro-organisms and tumour cells, respectively. The NO synthesizing pathway has been demonstrated in human monocytes and other cells, but its role in host defence seems to be accessory. A delicate functional balance between microbial stimuli, host-derived cytokines and hormones in the microenvironment regulates iNOS expression. This review will focus mainly on the known and proposed mechanisms of the regulation of iNOS induction, and on agents that can modulate NO release once the active enzyme has been expressed in the macrophage.